A pragmatic analysis on the types and the purposes of address terms used by the main character in Jane Austen’s “EMMA” - Miftahush Shalihah (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2018)
This research aims to describe the types of address terms used by the main character in Jane Austen’s EMMA and  to reveal the main character’s purposes in using types of address terms. Further, this study employs descriptive-qualitative method. The result of the research can be concluded as follows. First, there are 8 types of address terms. They are (a) title plus last name, (b) first name, (c) full name, (d) pet name, (e) kinship terms, (f) title plus full name, (g) occupational terms, and (h) title alone. The most frequent use of address terms is title plus last name since it is used to respect the addressees. Second, there are 6 purposes of address terms. They are (a) to show politeness, (b) to show intimacy, (c) to show social status, (d) to keep inferiority, (e) to show friendship, and (f) to show solidarity. From the study, the writer found that the address terms are mostly used in purpose to be polite to the addressees.   DOI: 10.26905/enjourme.v2i2.2747